2020
DOI: 10.1177/0954407020916562
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vaned diffuser on the potential effect of volute and stall inception of centrifugal compressor

Abstract: In the automotive turbochargers centrifugal compressor, the volute has a strong potential effect, leading to circumferential nonuniformity of the impeller flow field and compressor stall. In this study, full-annulus unsteady simulations for centrifugal compressors with vaned/vaneless diffusers are carried out. The influence of the diffuser vane on the potential effect of the volute and stall behavior of a centrifugal compressor is studied in detail. Based on the distribution of the casing static pressure, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Once one of these two phenomena was observed, the operating point was considered as stall and the previous converged mass flow rate was determined to be the compressor stall limit. 27 For the requirements of Spalart-Allmaras turbulence model, the value of inlet turbulent viscosity was set to 1e À04 m 2 /s, Fu et al 16 researched the same centrifugal compressor and proved that 1e À04 m 2 /s was suitable. All of the solid walls were assumed to be non-slip and adiabatic.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once one of these two phenomena was observed, the operating point was considered as stall and the previous converged mass flow rate was determined to be the compressor stall limit. 27 For the requirements of Spalart-Allmaras turbulence model, the value of inlet turbulent viscosity was set to 1e À04 m 2 /s, Fu et al 16 researched the same centrifugal compressor and proved that 1e À04 m 2 /s was suitable. All of the solid walls were assumed to be non-slip and adiabatic.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…13 The study of Yang et al 14 and Su et al 15 showed that the volute could determine both the static pressure distribution on the casing wall and the circumferential position of stall inception. Moreover, Fu et al 16 investigated the same centrifugal compressor with vaned/vaneless diffuser and found that the vaned diffuser reduces the potential effect of volute but could not eliminate the "locking effect" of stall inception. Nevertheless, for a turbocharger centrifugal compressor with high pressure ratio, the use of variable diffuser vanes could extend the stable operating range with an acceptable decline of aerodynamic performance, according to the study of Zheng.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Moreover, adding vanes with large stagger angles in the vaneless diffuser can weaken the potential interference of the volute to the upstream flow field and delay the compressor stall. 33 The essence of the above methods is to control the source of the pressure distortion. Suppose the pressure wave with circumferential distortion generated downstream can be cut off inside the impeller.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Many studies have proved that the volute causes flow field distortion in the diffuser, and this distortion propagates reversely in the diffuser and the impeller, which causes flow field distortion at the impeller inlet and induces the compressor stall. [11][12][13] The distribution of non-uniform flow field in the compressor can be reflected by evenly arranging static pressure probes in the circumferential direction to measure the static pressure distribution on the casing wall of the compressor. For a centrifugal compressor with volute applied in automobile turbocharger, Yang and Zhang [14][15][16] analyzed the casing-wall static pressure distribution under different rotational speeds and different operating conditions through experiments and calculations to understand its stall mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Many studies have proved that the volute causes flow field distortion in the diffuser, and this distortion propagates reversely in the diffuser and the impeller, which causes flow field distortion at the impeller inlet and induces the compressor stall. 1113…”
Section: Introductionmentioning
confidence: 99%